2013
DOI: 10.1038/srep02534
|View full text |Cite|
|
Sign up to set email alerts
|

Ligand modified nanoparticles increases cell uptake, alters endocytosis and elevates glioma distribution and internalization

Abstract: Nanoparticles (NPs) were widely used in drugs/probes delivery for improved disease diagnosis and/or treatment. Targeted delivery to cancer cells is a highly attractive application of NPs. However, few studies have been performed on the targeting mechanisms of these ligand-modified delivery systems. Additional studies are needed to understand the transport of nanoparticles in the cancer site, the interactions between nanoparticles and cancer cells, the intracellular trafficking of nanoparticles within the cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
193
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 272 publications
(208 citation statements)
references
References 42 publications
(55 reference statements)
13
193
0
2
Order By: Relevance
“…[50][51][52][53][54] Finally, as endocytosis of nanoparticles is an energy-dependent process, sodium azide (NaN 3 ) was used to deplete the energy demands for endocytosis and restrict metabolic activity. [62,63] FACS analysis revealed that Gen, Wor, and Noc had no adverse effect on the delivery of fluorescently labeled cytC (Figure 4a), whereas in the presence of Chl and NaN 3 , uptake of nanoparticles containing cytC was slightly lowered to 90% as compared to the initial experiment in the absence of inhibitors. To further study the role of CC formation on the mechanism of cellular uptake, we omitted the CP 4 K 4 pretreatment of HeLa cells in control experiments.…”
Section: Endocytosis and Micropinocytosis Inhibitors Marginally Affecmentioning
confidence: 91%
“…[50][51][52][53][54] Finally, as endocytosis of nanoparticles is an energy-dependent process, sodium azide (NaN 3 ) was used to deplete the energy demands for endocytosis and restrict metabolic activity. [62,63] FACS analysis revealed that Gen, Wor, and Noc had no adverse effect on the delivery of fluorescently labeled cytC (Figure 4a), whereas in the presence of Chl and NaN 3 , uptake of nanoparticles containing cytC was slightly lowered to 90% as compared to the initial experiment in the absence of inhibitors. To further study the role of CC formation on the mechanism of cellular uptake, we omitted the CP 4 K 4 pretreatment of HeLa cells in control experiments.…”
Section: Endocytosis and Micropinocytosis Inhibitors Marginally Affecmentioning
confidence: 91%
“…157 Therefore, we depleted the energy of the cortical neurons with sodium azide to inhibit endocytosis, an energy dependent process. 159 The addition of sodium azide reduced endocytosis of chitosan-coated MNPs by close to 90% but had no significant effects on starch-coated MNPs (Fig. 2b).…”
Section: Location and Uptake Of Mnpsmentioning
confidence: 99%
“…Nanocarriers have the capacity to enhance drug delivery by passive targeting due to the EPR effect in conjunction with their increased circulation half-life time. Several studies report that NPs are internalized into cancer cells through endocytosis ( Figure 6) [108,139,149]. Usually in biological environment serum proteins adsorb on NP surface facilitating the uptake mechanism by the formation of endocytic vesicles [139].…”
Section: Internalization Of Nanocarriersmentioning
confidence: 99%
“…Techniques such as transmission electron microscopy (TEM) and laser scanning confocal microscopy (LSCM) have been useful in understanding the mechanisms of NP uptake and toxicity [149,[151][152][153].…”
Section: Internalization Of Nanocarriersmentioning
confidence: 99%